Factors Associated With Delay in Cleft Surgery at a Tertiary Children's Hospital in a Major US Metropolitan City. (November 2021) - Stoneburner, Jacqueline; Munabi, Naikhoba C. O.; Nagengast, Eric S.; Williams, Madeleine S.; Goel, Pedram; Auslander, Allyn; Howell, Lori K.; Hammoudeh, Jeffrey A.; Urata, Mark M.; Magee, William P.
Objective: To identify factors associated with late cleft repair at a US tertiary children's hospital. Design: Retrospective study of children with CL/P using Children's Hospital Los Angeles (CHLA) records. Setting: US tertiary children's hospital. Patients/Participants: Patients undergoing primary CL or CP repair at CHLA from 2009 to 2018. Main Outcome Measures: Proportion of children who had delayed primary CL repair or CP repair using CHLA and American Cleft Palate-Craniofacial Association (ACPA) guidelines and factors associated with late surgery. Results: In total, 805 patients—503 (62.5%) who had CL repair, 302 (37.5%) CP repair—were included. Using CHLA protocol, 14.3% of patients seeking CL repair had delayed surgery. Delay was significantly associated with female gender, non-Hispanic ethnicity, Spanish primary language, government insurance, bilateral cleft, cleft lip and palate (CLP), and syndromic diagnosis. Using ACPA guidelines, 5.4% had delayed surgery. Female gender and syndromic diagnosis were significantly associated with delay and remained significant after adjustment for confounders in multivariate models. For CP repair, 60.3% of patients had delayed surgery using CHLA protocol. Cleft lip and palate diagnosis, complete cleft, syndromic diagnosis, and longer travel distance were significantly associated with delay. Using ACPA guidelines, 28.5% had delayed surgery; however, significant association with patient variables was not consistently observed. Conclusions: Delay in cleft surgery occurs most often for patients seeking CP repair and is associated with female gender, non-Hispanic ethnicity, Spanish language, government insurance, and bilateral CL, CLP, or syndromic diagnoses. Initiatives should aim to optimize cleft surgery delivery for these subpopulations.